"It is Only Watching, Waiting, Attention": Rethinking Love with Alain Badiou and Simone Weil (KEMANUSIAAN The Asian Journal of Humanities, 2015)
Love has traditionally been thought in conjunction with emotion, affect, passion and feelings. The work of Alain Badiou, however, challenges such an "anti-philosophical" position, and posits that the truly philosophical way to approach love is through logic, which also underscores loves close kinship to thought and to truth. In this essay, the author draws on Badiou's thoughts on love to theorise an amorous politics. Responding to critiques on Badiou's evental politics as essentially passive, the author suggests that the thought of Simone Weil offers a way to think of waiting as a pre-evental form of political agency. The author argues that positioning Badiou's thought with Weil's makes even more legible the political utility of his radical philosophy of love.